The coordination of amidoxime ligands with uranyl in the gas phase: a mass spectrometry and DFT study. Issue 41 (26th September 2016) - Qin, Zhen; Shi, Siwei; Yang, Chuting; Wen, Jun; Jia, Jianping; Zhang, Xiaofang; Yu, Haizhu; Wang, Xiaolin
Abstract : The coordination of three amidoxime ligands (NAO, GIO, and GDO) with uranyl was compared by MS studies and DFT calculations in the gas phase to reveal the structural information. Abstract : Sequestering uranium from the ocean is a promising solution to fulfill the demand for nuclear energy. Motivated by this purpose, a series of amidoxime ligands and their analogs have been developed with high absorption capacity and selectivity. An in-depth understanding of the structural information of the uranyl–ligand complexes is essential to improve the performance of the ligands. Herein, we have studied the coordination of three amidoxime ligands (6-methoxyl-naphtha-2-amidoxime, NAO; glutarimidedioxime, GIO; and gluardiamidoxime, GDO) with uranyl in the gas phase by mass spectrometry. The identifications of the electrospray ionization (ESI) generated species, the fragmentation pathways upon dissociation, the relative binding affinities of the ligands, and the hydration reactions have been conducted and compared to reveal their structural information in the gas phase. The binding modes for all the complexes were suggested based on the experimental results and were further studied by density functional theory (DFT) calculations.